Achieving net zero plus reliable energy supply in Germany by 2045: the essential role of CO2 sequestration - Dickel, R (Oxford Institute for Energy Studies, 2022)
The present German energy policy is focussed on further increase of renewable capacity and power consumption to achieve net zero GHG emissions by 2045 while maintaining security of energy supply. The planned pace of the rollout of renewables looks ambitious but feasible and could result in phasing out substantial volumes of unabated coal-fired power production by 2030. However, it will miss the net zero target in 2045 by decades even if the issues surrounding the low readiness level of electrolysis and yet-to-be-provided hydrogen infrastructure, especially storage, could be resolved in time. For a realistic chance to meet net zero in 2045 adding an ambitious CO2 capture and sequestration policy is essential. The present German legislation bars CO2 sequestration but CO2 capture and transport for export are explicitly possible. Norway with a sequestration potential of 70 Gt CO2 would be an obvious partner for Germany, but such a partnership would require the introduction of missing German standards and procedures to handle CO2 and ratifying the amendment of the London protocol by Germany. By adding a pragmatic CO2 sequestration policy such as those in the US, UK and the Netherlands, Germany would have a realistic chance to reach net zero by 2045 without jeopardizing its industrial basis.